Problematika Pengalihan Objek Jaminan Fidusia oleh Debitur: Studi Kasus PT. Buana Finance Kota Jambi - Nova Ridani, Silvana; Pahlefi, Pahlefi (Zaaken: Journal of Civil and Business Law, 2025)
This research aims to examine and analyze dispute resolution and the legal consequences of the agreement if the debtor transfers the fiduciary guarantee object underhand at PT. Buana Finance Jambi City. The problem formulation of this research, namely how is the settlement of the fiduciary guarantee object transferred by the debtor underhand in a consumer financing agreement at PT. Buana Finance Jambi City, and what are the legal consequences of a consumer financing agreement if the object of fiduciary guarantee is transferred by the debtor underhand at PT. Buana Finance Jambi City. This research is empirical research, the results of the study indicate that the settlement process for debtors who transfer the fiduciary guarantee object underhand at PT. Buana Finance Jambi City will be resolved using non-litigation dispute resolution or out of court. In the case of a consumer financing agreement, the agreement becomes cancelable